Surface Chemistry of Super-Hydrophilic SiO2-Doped TiO2 Photo-Catalysts for Self-Cleaning Glass - Lien, Shui-Yang; Nautiyal, Asheesh; Jhu, Jia-he; Hsu, Jen-Ken; Jen Lee, Shuo (Asian Journal of Chemistry, 2013)
The self-cleaning of glass surface can be enhanced by coating the photoinduced super-hydrophilic nanoporous thin film based on TiO2 photocatalysts via sol-gel process. In this article, a new method has been introduced to enhance the photocatalytic activity of TiO2 thin film, directly coated on the glass, developed by doping SiO2. The effects of post-annealing and the SiO2 content in TiO2 film on the photocatalytic activity were investigated. The microstructure and hydrophilic properties of the film were studied by using differential X-ray diffraction, field-emission scanning electron microscope. After illuminated by ultraviolet light, the SiO2 doped TiO2 film is super-hydrophilic with water contact angle less than 1º, this favours greatly the self-cleaning purpose of the glass surface.